Numerical Simulation of Electro-Thermal Properties in FDSOI MOSFETs Down to Deep Cryogenic Temperatures - Ghibaudo, Gerard; Balestra, Francis (Journal of Electronics and Electrical Engineering, 2023)
An original reformulation of the thermopower S, heat conductivity K and heat capacitance C in bulk silicon for electrons and phonons is first proposed. Closed-form analytical approximations for these coefficients as a function of Fermi level, temperature and/or carrier concentration are developed for implementation in Technology Computer-Aided Design (TCAD) simulation. These analytical expressions for S, K and C have been employed to simulate the electro-thermal properties of a Fully Depleted Silicon on Insulator (FDSOI) Metal-Oxide-Semiconductor Field-Effect Transistor (MOSFET) versus front gate voltage from room down to very low temperature. The obtained results allow discriminating the electron and phonon contributions to the whole properties. These analyses could be very useful to further performing TCAD simulations of FDSOI MOSFETs down to very low temperature for full assessment of electro-thermal performances.